2010
DOI: 10.1002/jsfa.4203
|View full text |Cite
|
Sign up to set email alerts
|

Italian ryegrass silage in winter feeding of organic dairy cows: forage intake, milk yield and composition

Abstract: Italian ryegrass was indeed found to be highly palatable, confirming in principle its suitability as feed for organic dairy cows. However, higher energy and protein concentrations in this forage would be necessary to translate the high intakes of Italian ryegrass silage into improved milk production as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…Nitrogen efficiency, defined as the percentage of N in the milk compared with N intake, did not differ between the 2 groups (24.1%). This is in accordance with the results of Baldinger et al (2011), who reported N efficiencies between 24.6 and 24.7% under similar feeding conditions. Powell et al (2010), however, described a potential N efficiency between 30 and 35%.…”
Section: Nutrient Balances Efficiency Of Milk Production and Feed Vsupporting
confidence: 93%
See 2 more Smart Citations
“…Nitrogen efficiency, defined as the percentage of N in the milk compared with N intake, did not differ between the 2 groups (24.1%). This is in accordance with the results of Baldinger et al (2011), who reported N efficiencies between 24.6 and 24.7% under similar feeding conditions. Powell et al (2010), however, described a potential N efficiency between 30 and 35%.…”
Section: Nutrient Balances Efficiency Of Milk Production and Feed Vsupporting
confidence: 93%
“…These differences can be explained by the higher CP content of the control mixture, because dietary CP content has been detected as the main nutritional factor influencing milk urea content (Nousiainen et al, 2004). The general level of milk urea observed in the current experiment (21.6 and 18.4 mg/100 mL) was within the desired range of 15 to 30 mg/100 mL, indicating an adequate protein and energy supply (Sawa et al, 2011) and in agreement with the findings of Baldinger et al (2011), who observed milk urea contents of 18.5 and 19.9 mg/100 mL. Most of the blood metabolites and haptoglobin were not affected by the concentrate type.…”
Section: Milk Production and Concentrations Of Physiological Blood Vasupporting
confidence: 88%
See 1 more Smart Citation
“…), which is an important forage crop in temperate regions (Baldinger et al . ; Kaneko et al . ; Popay et al .…”
Section: Introductionmentioning
confidence: 99%
“…originated in the Mediterranean region and is produced mainly for hay and silage. It is one of the most important forage grasses in the temperate zones of Europe and Asia because of its high palatability to and digestibility by livestock [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%